A new method for evaluation of motor injury after acute brain ischemic damage. (1st June 2015) - Hu, Zeng-Chun; Ma, Hui; Fan, Qing; Yin, Jian; Wei, Ming-Hai; Lin, Yong-Zhong; Fan, Ming; Sun, Chang-Kai
<x xml:space="preserve">Abstract</x> Purpose: Motor impairment is an important index for assessing the extent of brain injury. The present study uses a new method, the movement capture analysis (MOCA) system, for assessing motor damage after acute ischemia. Materials and Methods: Forty rats were divided into four groups: standard ischemia, sham-operated, Dizocilpine (MK-801), and Ginkgo biloba extract (GBE) groups. Brain ischemia was induced using the temporary right middle cerebral artery occlusion model. Longa score and MOCA were used to assess motor injury one day after ischemia. Infarct volume was delineated with 2% 2, 3, 5-triphenyltetrazolium chloride (TTC) staining. The correlation of infarct volume with Longa score and MOCA data was calculated. Results: Compared with the sham-operated group (0.10 ± 0.31), Longa scores of MK-801 (2.33 ± 0.73), GBE (1.80 ± 0.58), and standard (2.88 ± 0.83) groups showed a statistical difference (p < 0.05); however, it was unable to discern the difference between MK-801 and standard groups. MOCA was able to clearly discern the differences in motor disparity among the four groups, standard (1.00 ± 0.19), sham-operated group (0.17 ± 0.02), MK-801 (0.79 ± 0.08), GBE (0.38 ± 0.05) (p < 0.05). Both MK-801 (18.03 ± 0.96%) and GBE (10.82 ± 1.93%) treatment reduced infarct size compared with the standard ischemia group (25.88 ± 1.16%) (p < 0.05). The MOCA data showed a more significant correlation with infarct size than Longa score (r = 0.85:0.53). Conclusions: MOCA system proved to be more sensitive than the Longa score. It may potentially be more accurate method for behavioral evaluation in clinical trials.